Equilibrium thermodynamics - Adkins, C. J. (Cambridge University Press, 1983)
Equilibrium Thermodynamics gives a comprehensive but concise course in the fundamentals of classical thermodynamics. Although the subject is essentially classical in nature, illustrative material is drawn widely from modern physics and free use is made of microscopic ideas to illuminate it. The overriding objective in writing the book was to achieve a clear exposition: to give an account of the subject that it both stimulating and easy to learn from. Classical thermodynamics has such wide application that it can be taught in many ways. The terms of reference for Equilibrium Thermodynamics are primarily those of the undergraduate physicist; but it is also suitable for courses in chemistry, engineering, materials science etc. The subject is usually taught in the first or second year of an undergraduate course, but the book takes the student to degree standard (and beyond). Prerequisites are elementary or school-level thermal physics